Sonographic Evaluation of Renal Length, Cortical Echogenicity and Renal Thickness of Suspected Glomerulonephritis Patients Undergoing Renal Biopsy to Predict Irreversible Renal Parenchymal Disease and Comparison with Histopathology (Bangladesh Journal of Radiology and Imaging, 2026)
Background: Renal parenchymal disease is a growing global public health concern. Renal biopsy remains the gold standard for evaluating renal parenchymal disease, particularly in cases of nephrotic syndrome, proteinuria, glomerular hematuria. However, ultrasonography offers a noninvasive method to assess renal morphology. Objective: To correlate renal ultrasonographic parameters with histopathology in predicting irreversible renal parenchymal disease. Methods: This cross-sectional study conducted over two years (March 2022 to February 2024) includes 82 adult patients (³18 years),in the Department of Radiology and Imaging who were referred for image-guided renal biopsy. Renal sonographic findings were compared to biopsy findings, including glomerular sclerosis, interstitial inflammation, fibrosis, and tubular atrophy. Results: Most of the patients were middle aged and with a predominance of comorbid condition like hypertension (67.1%) and diabetes  mellitus (54.9%). Grade 2 renal cortical echogenicity was the most common sonographic finding (58.5%). Renal cortical echogenicity demonstrated strong positive correlations with glomerular sclerosis (r = 0.568), interstitial inflammation (r = 0.493),interstitial fibrosis (r = 0.365), and tubular atrophy (r = 0.394), all statistically significant (p < 0.001). Renal length showed significant inverse correlations with these histopathological parameters (r ranging from -0.231 to -0.521; p